187k views
4 votes
Solve for x. Ax + By = −C

x equals the quantity negative B times y minus C all over A
x equals the quantity negative B times y plus C all over A
x equals the quantity B times y plus C all over A
x equals the quantity B times y minus C all over A

User Basil Jose
by
5.2k points

2 Answers

4 votes
Your answer is the first option, x equals negative B times y minus C all over A.

To answer this it would be helpful to rearrange the equation to get it in the form “x =“:
Ax + By = -C
Ax = -C - By
x = (-C - By)/A
which we can also write as
x = (-By - C)/A

So now that we know what x equals we just have to write it in word form. We can see that both B and C are negative, which rules out all of the options except for the first one.
This is because in the second option, it says “plus C”, which implies C is positive.
In the third option, it says “the quantity B” instead of “the quantity negative B”, which implies that B is positive. This is also true for the last option.

This means that the first statement is the only one that could be true, so that’s the answer.
I hope this helps!
User Domguinard
by
5.5k points
6 votes

Answer:


\large\boxed{x=(-By-C)/(A)}

x equals the quantity negative B times y minus C all over A

Explanation:


Ax+By=-C\qquad\text{subtract}\ By\ \text{from both sides}\\\\Ax+By-By=-By-C\\\\Ax=-By-C\qquad\text{divide both sides by}\ A\\eq0\\\\(Ax)/(A)=(-By-C)/(A)\\\\x=(-By-C)/(A)

User Michel Rouzic
by
5.3k points